2016
DOI: 10.1071/ch15806
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Polymer Interlayer Modified ITO Electrodes for Organic Solar Cells

Abstract: Indium-tin-oxide (ITO) electrode surfaces were modified using thin polymeric films of ethoxylated polyethylenimine (PEIE) and poly(3,3′-([(9′,9′-dioctyl-9H,9′H-[2,2′-bifluorene]-9,9-diyl)bis(4,1-phenylene)]bis(oxy))bis(N,N-dimethylpropan-1-amine)) (PFPA-1) to investigate the resultant work function and its stability in ambient atmosphere. Both PEIE and PFPA-1 were found to significantly reduce the ITO work function, as a result of a surface dipole at the ITO–polymer interface. After aging for two weeks in ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Figure shows the shift in the secondary electron cutoff of the ultraviolet photoelectron spectroscopy (UPS) spectra and schematically depicts the corresponding vacuum level shift at the ITO–PNDIT10N interface, as a result of surface modification. The observed reduction in the work function agrees well with literature values for amino-containing interface materials with tertiary amine or pyridine pendant groups. ,,,,, This notable work function reduction is related to the free electron pair on the nitrogen in the PNDIT10N side group forming an interfacial dipole . This interfacial dipole further facilitates the electron collection and transport from the BHJ layer to the ITO cathode …”
Section: Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Figure shows the shift in the secondary electron cutoff of the ultraviolet photoelectron spectroscopy (UPS) spectra and schematically depicts the corresponding vacuum level shift at the ITO–PNDIT10N interface, as a result of surface modification. The observed reduction in the work function agrees well with literature values for amino-containing interface materials with tertiary amine or pyridine pendant groups. ,,,,, This notable work function reduction is related to the free electron pair on the nitrogen in the PNDIT10N side group forming an interfacial dipole . This interfacial dipole further facilitates the electron collection and transport from the BHJ layer to the ITO cathode …”
Section: Results and Discussionsupporting
confidence: 87%
“…The observed reduction in the work function agrees well with literature values for amino-containing interface materials with tertiary amine or pyridine pendant groups. 12,17,29,48,57,58 This notable work function reduction is related to the free electron pair on the nitrogen in the PNDIT10N side group forming an interfacial dipole. 9 This interfacial dipole further facilitates the electron collection and transport from the BHJ layer to the ITO cathode.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance and stability of these solar cells are known to be highly sensitive to moisture and oxygen. Sharma et al [ 1 ], for example, showed that the stability of the OPV cells was strongly affected by the moisture level. After ageing for two weeks in an ambient air atmosphere, the power conversion efficiency (PCE) of the cells dropped rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…include a report from plenary speaker Professor Mats Andersson on the 'Stability of Polymer Interlayer Modified ITO Electrodes for Organic Solar Cells'. [1] A highlight paper by invited keynote speaker Professor Christine Luscombe entitled 'Poly(3-hexylthiophene) End-Functionalization via Quenching Resulting in Heteroatom-Bond Formation' illustrates how changing the end-functional groups of P3HT to incorporate chalcogens opens up the opportunity to control and alter interactions with different materials. [2] Two review articles from early career researchers include Dr Katherine Locock's (CSIRO, Melbourne, Australia) review entitled 'Bioinspired Polymers: Antimicrobial Polymethacrylates' which traces the development of the antimicrobial polymethacrylates from the initial mimicry of global cationic and lipophilic AMP properties through to the level of specific amino acids present in the peptides.…”
mentioning
confidence: 99%